PENETAPAN KADAR STEVIOSIDA PADA SIMPLISIA DAN EKSTRAK DAUN Stevia rebaudiana DARI TIGA DAERAH BERBEDA - Dian Kartikasari; Nurkhasanah Nurkhasanah; Suwijiyo Pramono (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2018)
ABSTRACTPharmaceutical raw materials from agriculture or collection of wild plant chemical content can not be guaranteed always constant due to variable seed, the body, the climate, the conditions (age and how to harvest). The content of the chemical compounds responsible for the biological response must have chemical specifications, namely the composition information (type and concentration). The efficacy of traditional medicine based on the chemical compound. Therefore, the assay of the active substance a crude drugs and extracts needs to be done to ensure that a traditional medicinal products can be assured of quality and usefulness. The assay performed on botanicals and 50% ethanol extract of leaves of Stevia rebaudiana. The assay of the crude drugs and extracts from the stevia leaf area of Malang, Tawangmangu, and Bogor using High Performance Liquid Chromatograph method. Results of the assay stevioside on simplicia and stevia leaf extract obtained stevioside levels in simplicia stevia leaves from Malang, Bogor, Tawangmangu consecutive namely 5.65%; 3.89%; 1.59%. Stevioside levels in the stevia leaf extract of Malang, Bogor, Tawangmangu respectively, are 14.14%; 22.40%; 66.65%.Key word: Stevia rebaudiana leaf, stevioside content, High Performance Liquid Chromatograph